Sekolah Kepemimpinan Aparatur Desa Perempuan pada Desa Cikumpay, Kabupaten Purwakarta - Reza, Izzul Fatchu; Rahmawati, Auli; Istania, Ratri (Civitas Consecratio: Journal of Community Service and Empowerment, 2024)
Purwakarta District values gender diversity with the presence of a female regent and ten female village heads. However, the competence and leadership skills are not evenly owned by all female village heads in Purwakarta Regency. The purpose of this Community Service activity is to increase understanding and awareness of the importance of women leaders at the village government level. This community service uses an audienced-centered simulation approach for village officials in Cikumpay Village led by a female village head. After the implementation, the community stated that community service activities were very useful (77.8%) and quite useful (22.2%). In addition, women should be given the opportunity to have the space to work and appear in the offices of public agencies, including becoming leaders.